Description of Community Knowledge, Attitudes and Behavior Regarding Dengue Hemorrhagic Fever in Namasina Village, Central Maluku Regency - Yosephin Sri Sutanti; Yusuf Handoko; Aulia Fitri Swity; Sani Euodia Laelaem; Antonius DR Manurung (Jurnal MedScientiae, 2023)
Dengue Haermorrhagic Fever (DHF) is a global health problem in tropical and subtropical regions, as well as endemic in the world. The cases of DHF in Mollucas, based on data of Health Office has increased significantly. The aim of this research is to determine the knowledge, attitude and behaviour of society about DHF. This study using a cross sectional design with a questionnaire as an instrument of research, conducted on 97 respondents, which is taken by cluster sampling. The results showed 83,5% (81 people) had good knowledge and 16,5% (16 people) intermediate, 89,7% (87 people) of respondents had good attitude and 10,3% (10 people) intermediate, and about 6,2% of respondents had poor behaviour. It could be concluded that a good or fine knowledge and attitude doesn’t always result in a good or fine behaviour.